Penerapan Pembelajaran Science Technology Engineering and Mathematics (STEM) dalam Meningkatkan Keaktifan Belajar Anak Usia Dini - Eritha Riawati; Kemas Imron Rosadi; Mahluddin Mahluddin (Center for Religious Studies and Social Empowerment Foundation, 2022)
This study aims to find out how the STEM learning model is implemented and what are the obstacles to implementing the learning model. This study uses a descriptive qualitative approach by collecting data through observation, interviews, and documentation. The technical stages of data analysis included data reduction, data presentation and data verification, while checking the reliability of the data was carried out by extending participation, accuracy of observations, triangulation and consulting supervisors. The results of the study show that the STEM learning model in the future for Al Aliyya's playgroup education has implemented a STEM learning model where learning is child-centered so that children are more active in thinking and solving the problems they face. The application of STEM learning in Al Aliyya's play group is in the form of physical motor activities, storytelling, sensory, construction play, role play, science play, art, cooking, and literacy. While the STEM learning constraints are in the form of inefficient use of time, there are differences in character or learning attitudes of children who want to win alone with what they want to play, so that it is not uncommon to fight over toys even though before playing the educator has given a foothold and has made an agreement with the child about the rules of the game. Penelitian ini bertujuan mengetahui bagaimana penerapan model pembelajaran STEM serta apa saja kendala penerapan model pembelajaran. Penelitian ini menggunakan pendekatan kualitatif deskriftif dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Tahap teknik analisis data meliputi reduksi data, penyajian data dan verifikasi data, sedangkan pengecekan keterpercayaan data dilakukan dengan perpanjangan keikutsertaan, ketelitian pengamatan, triangulasi dan melakukan konsultasi ke pembimbing. Hasil penelitian menunjukkan bahwa model pembelajaran STEM ke depan terhadap pendidikan kelompok bermain Al Aliyya sudah menerapkan model pembelajaran STEM di mana pembelajaran berpusat pada anak sehingga anak lebih aktif dalam berpikir dan memecahkan permasalahan yang mereka hadapi. Penerepan pembelajaran STEM di kelompok bermain Al Aliyya berupa adanya kegiatan fisik motorik, bercerita, sensorial, bermain konstruksi, bermain peran, bermain sains, seni, memasak, dan literasi. Sedangkan faktor kendala pembelajaran STEM berupa penggunaan waktu yang kurang efisien, adanya perbedaan karakter berupa atau sikap belajar anak yang mau menang sendiri dengan apa yang ingin dimainkannya, sehingga tidak jarang terjadi berebutan mainan walaupun sebelum main pendidik sudah memberikan pijakan main dan sudah membuat kesepakatan dengan anak tentang aturan main.